Time series databases new ways to store and access data - Dunning, Ted; Friedman, B. Ellen (O'Reilly Media, 2015)
Time series data is of growing importance, especially with the rapid expansion of the Internet of Things. This concise guide shows you effective ways to collect, persist, and access large-scale time series data for analysis.